2013
DOI: 10.1161/circheartfailure.113.000414
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Magnetic Resonance Characteristics in Children With Hypertrophic Cardiomyopathy

Abstract: Background-Cardiovascular magnetic resonance has provided important information on the diagnosis and risk stratification of hypertrophic cardiomyopathy (HCM) in adults; however, comparable data are absent for HCM in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
53
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 25 publications
5
53
2
Order By: Relevance
“…Late Gadolinium Enhancement on Cardiac Magnetic Resonance (CMR) imaging 3 studies 38,39,40 were identified that looked at the predictive value of late gadolinium enhancement on CMR as a risk factor for SCD in childhood HCM. They reported an increased incidence of LGE in patients with adverse outcomes.…”
Section: Hour Blood Pressure Monitoring 13mentioning
confidence: 99%
“…Late Gadolinium Enhancement on Cardiac Magnetic Resonance (CMR) imaging 3 studies 38,39,40 were identified that looked at the predictive value of late gadolinium enhancement on CMR as a risk factor for SCD in childhood HCM. They reported an increased incidence of LGE in patients with adverse outcomes.…”
Section: Hour Blood Pressure Monitoring 13mentioning
confidence: 99%
“…The imaging protocol and analysis have been described previously. 18,19 Briefly, a true fast imaging with steady-state precession (TrueFisp) sequence was used to obtain cine images, which included LV 2-chamber and 4-chamber long-axis view, LVOT view, and LV short-axis views (contiguous slices from atrioventricular ring to apex).…”
Section: Methodsmentioning
confidence: 99%
“…The most important application is the detection and grading of the severity of myocardial fibrosis, which appears to be an important risk factor for subsequent ventricular arrhythmias and sudden cardiac death in both adults and children (1,2,16).…”
Section: Workup and Diagnosismentioning
confidence: 99%